A shot in the volcano; A humorous travelogue about Java by Dé-Lilah (1896) - Praamstra, Olf (UI Scholars Hub, 2024)
In 1899 Dé-Lilah, pseudonym of Lucy van Renesse-Johnston (1862-1906), published a travel story in two parts, Mevrouw Klausine Klobben op Java (Mrs Klausine Klobben on Java). It was an account of an early tourist trip she had made in 1896. According to Van Renesse, she undertook her journey to do environmental research on Java as well as ethnographic research on the native and European inhabitants of the island. But that was just a pretext for a woman who travelled alone to climb volcanoes, visit shrines and talk to the various inhabitants of Java. She was able to do so because as a Eurasian woman, in addition to Dutch, she spoke fluent Malay. But contrary to her claims, it was never her intention to write a scientific travelogue. From the very beginning, she wanted to write a humorous travel story along the lines of the popular German author Julius Stinde (1841-1905). By taking his work as an example, she wrote a satirical story about travel on Java, at a time when tourism had hardly begun in the Netherlands East Indies.